Aesthetic and functional rehabilitation in a patient with anterior skeletal open bite using lithium dissilicate glass-reinforced ceramic: a case report (Research, Society and Development, 2022)
The aim of this clinical report is to present the replacement of unsatisfactory metal-ceramic crowns of elements 12, 11, 21 and 22, by lithium disilicate glass-reinforced ceramic crowns in a patient with skeletal anterior open bite. A patient sought care at the Dental Hospital at the School of Dentistry of UFU, complaining of odor between the metal-ceramic crowns of the antero-superior teeth. After clinical and radiographic examination, invasion of the biological space was noticed, surgery was indicated in order to restore the biological space. After healing, the pre-existing cast metal posts were masked using an opaque composite resin and the teeth were reprepared for full all-ceramic crowns. Impressions were taken in two steps, using PVS associated to retraction cords. The ceramic copings were obtained in lithium disilicate ceramic, and the veneering was performed by stratification. After testing the ceramics crowns in relation to, fit, function and aesthetic results, cementation was completed using modified absolute isolation, followed by prophylaxis of preparations with pumice and saline, surface treatment of the ceramic restorations and luting using self-adhesive resin cement. Finally, an occlusal splint was produced to control the effects of bruxism and orofacial pain symptoms. The anterior open skeletal bite was a challenging factor for the rehabilitation of this patient; however, one must consider the entire process that the patient would undergo if choosing for orthognathic surgery, and the patient should be aware of the case limitations. In addition, the use of lithium disilicate glass-reinforced ceramics proved the versatility of this material for anterior aesthetic restorations.